The Effect of Heating Temperatures on the Formation of Vanillin from Curcumin - Sunardi, Riyana; Syukri, Daimon; Sylvi, Diana; Azima, Fauzan (Open Global Scientific Journal, 2025)
Background: Food additives are components added to food to change or affect the shape, characteristics, or properties of food products. Vanillin is one of the flavors widely used in food, perfume, and cosmetic industries. Natural vanillin is obtained from Vanilla planifolia through vanilla bean extraction, but this production is limited so that alternative methods, such as chemical synthesis and biotechnological technique, are increasingly used. Curcumin from the rhizomes of turmeric plant (Curcuma longa) can be degraded into vanillin through a degradation process.Aims & Methods: This study aims to explore the degradation process of curcumin into vanillin using ethanol solvents at temperatures of 50, 60, and 70°C. The parameters analyzed were color changes using colorimetry, curcumin content using spectrophotometry, and vanillin content using HPLC.Results: The results show that increasing the treatment temperature caused a significant decrease in curcumin content and an increase in vanillin content. The heating temperature of curcumin affected the curcumin content, although it did not affect the color intensity and vanillin content formed. Vanillin was not formed by heating curcumin at the temperatures of 50, 60, and 70oC. A temperature of 60°C resulted in the formation of significant vanillin content.